(untitled) (The East and Central African Journal of Pharmaceutical Sciences, 2018)
This study was undertaken to investigate the role played by pharmacists in the use of veterinary pharmaceutical products in Harare and Chitungwiza, Zimbabwe. A sample of 32 retail pharmacists participated in the study. Twenty-four pharmacists (75 %) stocked and handled a mean of 2.8 veterinary pharmaceutical products per month and 83 % of them rated their knowledge of use of these products as being poor or little. 66 % of pharmacists did not feel competent handling the products. Sixty two percent of pharmacists had prepared veterinary pharmaceutical products before and 38 % had never done this. Pharmacists’ competence in handling veterinary pharmaceutical products was associated with stocking this group of products (p<0.05). Pharmacists felt professionally ill-equipped to handle these products and subsequently only stocked a limited range of the products. Pharmacists need to play a more prominent role in the use and dispensing of veterinary pharmaceutical products for the betterment of animal health.